Exames nacionais.: A influência de pequenos factores - Leal, João Paulo (Revista da Associação Portuguesa de Linguística, 2019)
To construct external examinations is a complex and very serious matter. It is necessary time and the contribution of many people with complementary skills, who are specialists in various subjects (scientific, pedagogical and technical ones). Despite all this effort, a test always depends on many small factors. Small changes in quotations, the way one asks a question or the type of question chosen can have very marked effects in the grades of a test. Whatever the subject in analysis the fundamental question is: what are the national examinations for? If the examinations are to be the end of a cycle, i.e. the completion of secondary education, the way questions are placed and the distribution of quotations must follow a certain pattern if the examinations are meant to select students to access higher education the approaches to assume will be completely different. The option of using national exams as a way of select students to access higher education has been hijacking teachers who increasingly feel pressure to prepare students for exams instead of providing students with knowledge and skills. Universities and Polytechnics should assume their responsibilities and, in coordination with the Ministry of Education, take the initiative to select the students for Higher Education by releasing the national exams to fulfill their task, certifying the end of a cycle.